Sea turtles of the Atlantic and Gulf coasts of the United States - Ruckdeschel, Carol (Wormsloe Foundation nature book., 2006)
Describes the physical characteristics, natural environment, behavior, and conservation of sea turtles that can be found along the Atlantic and Gulf Coasts of the United States. Includes photographs, illustrations, and distribution maps.